Perencanaan Proyek Pemasangan Jalur Pipa Angin dan Kompresor pada beberapa Mesin Produksi di PT X - Ibrahim, Attar; Murnawan , Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
A contractor is a party hired to complete a job. CV. Andhika Kencana is a contractor who has received wind pipe installation projects ranging from compressor machines to production machines. PT Compressor pipe installation is used to run automotion machines in the production area. Pressurized air is produced from the compressor which will later be connected to pipes until it reaches the automotion machines. The problem here is how to schedule pipe installation so that it is on time and in accordance with the budget that has been determined at the beginning. The methods used in this research are the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT). The results obtained are that the critical path in this project is activities A, B, D, F, H, I, K, M, N, O, and the probability that the wind pipe installation project can be completed in 60 days is 27.09%.